Digital manipulation and mass mobilization over the long run: evidence from Latin America - Alcántara-Lizárraga, José Ángel; Jima-González, Alexandra (Frontiers in Political Science, 2024)
False information flows through social media are a worldwide phenomenon, affecting Latin America in particular, where more than 70% of internet users report growing concern regarding the circulation of fake news, especially through social media platforms. Although the academic literature has studied how governments may be incentivized to disseminate false information, it has concentrated in the electoral context mostly. In this sense, the impact of disinformation on mass mobilization patterns has been less explored, although it is relevant: manipulation through social media can reduce citizens' inclination to protest by directly influencing their preferences or beliefs about the government, acting as a preventive digital repression tool. In fact, governments have efficiently used it in the short run; however, it has not been established if this strategy could work in the long run. Hence, this article explores the long-term relationship between manipulation by the government through social media and the occurrence of mass mobilization to determine whether they are cointegrated. Drawing on the most recent literature on digital repression, manipulation, and mass mobilization and by applying a panel cointegration methodology in nine countries in Latin America (2000–2021), we find that the variables are cointegrated. In addition, we explore the causal (Granger) effect and find a unidirectional link that goes from social media manipulation to mass mobilization.